2017
DOI: 10.1002/1873-3468.12943
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics, mitophagy and biogenesis in neonatal hypoxic‐ischaemic brain injury

Abstract: Hypoxic-ischaemic encephalopathy, resulting from asphyxia during birth, affects 2-3 in every 1000 term infants and depending on severity, brings about life-changing neurological consequences or death. This hypoxic-ischaemia (HI) results in a delayed neural energy failure during which the majority of brain injury occurs. Currently, there are limited treatment options and additional therapies are urgently required. Mitochondrial dysfunction acts as a focal point in injury development in the immature brain. Not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 191 publications
0
42
0
Order By: Relevance
“…Though examination of the global fetal cortical transcriptomic changes 24 hours after OXT did not reveal involvement of specific hypoxia-associated pathways, there was a preponderant differential expression of genes from the mitochondrial ETC. Taken together with the central role of brain mitochondria in responding to hypoxic and oxidative stress (38)(39)(40)(41), and the brain region-specific persistent alteration of mitochondrial ETC proteins in juvenile offspring, we determined that one of the major effects of OXT-induced uteroplacental ischemia was oxidative stress with possible mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Though examination of the global fetal cortical transcriptomic changes 24 hours after OXT did not reveal involvement of specific hypoxia-associated pathways, there was a preponderant differential expression of genes from the mitochondrial ETC. Taken together with the central role of brain mitochondria in responding to hypoxic and oxidative stress (38)(39)(40)(41), and the brain region-specific persistent alteration of mitochondrial ETC proteins in juvenile offspring, we determined that one of the major effects of OXT-induced uteroplacental ischemia was oxidative stress with possible mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated that mitochondrial dynamics play an important role in regulating mitophagy [ 22 24 ]. Mitochondrial fission is a response to multiple stimulations and age-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…HI injury might reduce mitochondrial fusion, as indicated by decreased expression of the fusion proteins MFN1 and the long form of OPA1, and might increase mitochondrial fission, as indicated by downregulation of P-DRP1. Indeed, published results suggest that HI reduces mitochondrial fusion and increases mitochondrial fission to aggravate neonatal brain injury 23,24,55,56 . However, no significant differences in proteins regulating mitochondrial fusion or fission were found between the WT and AIF Tg mice after HI, suggesting that the aggravation of HI injury in the neonatal brain due to excessive AIF expression is unlikely to be related to changes in mitochondrial dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial morphology is dynamically controlled by a balance between organelle fission and fusion 21 , and this dynamic equilibrium can be disrupted by AIF deficiency 22 . Studies show that mitochondrial dynamics can be disrupted by HI injury in the immature brain and by ischemia/reperfusion in the adult brain 18,[23][24][25][26][27] . Thus, mitochondrial dynamics might be related to the pathophysiological processes of HI-induced brain injury.…”
Section: Introductionmentioning
confidence: 99%